Pengembangan Sistem Informasi Pengelolaan Usaha Laundry Berbasis Desktop - Sembiring, Afen Prana Utama; Kristian Telaumbanua; Erlanie Suparnap (STMIK Budi Darma, 2024)
The application of information systems can improve the scope of business capabilities by increasing the efficiency of each stage in a business activity. The purpose of this study is to create a desktop-based information system that focuses on laundry business management. Recording customer information, service transactions, financial management, and employee issues are some of the problems found. In addition to providing clear guidance for users, this system is designed to improve operational accuracy and efficiency in information management. This application will be developed using the System Development Life Cycle (SDLC) method using the C# programming language and using the SQL Server database. To meet the specific needs of the laundry business, the main modules to be integrated will include sales, purchasing, inventory, and human resource management. Thorough testing will be carried out prior to implementation to ensure ideal system performance. It is expected that the implementation of this system will improve operational effectiveness, more structured financial management, and better monitoring of inventory and employee management. Overall, this study targets the provision of information technology solutions that can overcome the main problems in managing a laundry business efficiently and effectively. The results of the design and development of this information system are in the form of a process design in the form of DFD, input design and report output design that are adjusted to the conditions and needs of the laundry company.